Nainen. - Koivuniemi, Paula, 1947-; Toivanen, Mika, 1970-; Vainio, Ilkka, 1960-; Aaltonen, Tapio, 1961-; Kuorikoski, Pekka; Lappalainen, Matti; Nykänen, Anssi, 1965-; Pohto, Heikki; Rantanen, Harri, 1960-; Tiirikainen, Jukka; Tuhkala, Marika, 1973-; Wäinölä, Tuomas, 1976-; et al. (Helsinki : Edel Records Finland, 2009)
1 kappale.
Julkaisussa teksti: Only for promotional use.
Mika Toivanen (tuottaja).
Paula Koivuniemi (lauluääni), Anssi Nykänen (rummut), Harri Rantanen (basso), Mika Toivanen (kosketinsoittimet), Tuomas Wäinölä (kitarat), Mongo Aaltonen (lyömäsoittimet), Jukka Tiirikainen (trumpetti), Matti Lappalainen (pasuuna), Heikki Pohto (saksofoni), Pekka Kuorikoski (taustalaulu), Marika Tuhkala (taustalaulu).
Keywords: tanssimusiikki; viihdemusiikki; tanssimusiikki; viihdemusiikki